Improving Parental Knowledge through Parenting Counseling in Wage Village, Taman District - qurrotul, ervyana; Dwi Masita , Elly; Rahma, Aisha Safira; Siska Prianti (Universitas Nahdlatul Ulama Surabaya, 2025)
Parenting education programs are widely promoted as a means of improving parental practices and supporting early childhood development. However, evidence regarding their comprehensive impact on children’s emotional and social development remains mixed. This study aims to critically assess the effectiveness of a short-term parenting education intervention in modifying parenting patterns and influencing emotional development outcomes among children aged 1–5 years in Wage Village, Taman District, Sidoarjo Regency. A quasi-experimental design with a one-group pretest–posttest approach was employed. Fivety parents were recruited using purposive sampling. Participants completed a validated questionnaire measuring two dimensions of parenting (authoritative and authoritarian) and five indicators of children’s emotional development. The intervention consisted of a 20-minute counseling session on positive parenting strategies. Data were analyzed using paired sample t-tests with a significance level of α = 0.05. Findings revealed a statistically significant reduction in authoritarian parenting scores (p = 0.000) and improvements in certain child emotional indicators, specifically behavioral problems and hyperactivity (p < 0.005). However, no significant changes were observed in peer relationships (p = 0.398) or prosocial behavior (p = 0.185). While the intervention showed measurable short-term effects on reducing rigid parenting styles and some behavioral issues, its influence on children’s social competencies remained negligible. These results suggest that short-term parenting education may be effective for addressing immediate behavioral concerns but is insufficient for fostering comprehensive social and emotional growth. Factors such as peer interaction, school environment, and cultural context likely play a stronger role in shaping these aspects. Sustainable, multi-sector strategies integrating community engagement, school-based programs, and ongoing parental support are recommended. Parenting education should be implemented as part of a broader, long-term framework to ensure lasting improvements in both parental practices and children’s holistic development.